Closed trans-intersphincteric fistulotomy: a new modified sphincter-sparing technique for high transsphincteric anal fistula - Chen, Bo; Wang, Yueting; Mei, Zubing; Mao, Chang; Liu, Yicheng; Zhao, Wenjun; Li, Yingying; Ye, Qianqian; Xu, Jin; Wang, Qingming (Frontiers in Surgery, 2024)
BackgroundThe main goals of surgery for fistula-in-ano are to completely resolve the condition and maintain optimal anal function. Effective management of the internal opening during and proper postoperative drainage of the intersphincter plane are crucial for achieving successful outcomes. This study evaluated the clinical efficacy of a novel sphincter-sparing technique for treating high transsphincteric anal fistula (HTAF).MethodsThis prospective study included 55 patients with HTAF who underwent closed trans-intersphincteric fistulotomy (CTiF) between July 2021 and April 2022 at our institution. Preoperative anorectal magnetic resonance imaging was performed for all patients. The primary outcome measures assessed the rate of fistula healing while the secondary outcome measures evaluated healing time, Cleveland Clinic Florida fecal incontinence score (CCF-FIS), 11-point visual analog scale (VAS) pain score and postoperative complications.ResultsWe included 55 patients with HTAF in this study. During a mean follow-up period of 9.3 months, CTiF achieved a healing rate of 90.91% (50/55). The mean time to recovery was 7.09 ± 1.94 weeks. Four (7.27%) patients developed postoperative urinary retention. At the 6-month follow-up, the CCF-FIS and VAS score were 0 [(0,0) range, 0–3] and 0 [(0,1); range, 0–4], respectively. Two patients with recurrent HTAF recovered after treatment with a transanal opening of intersphincteric space procedure, and three recovered after seton placement.ConclusionsCTiF is a promising and effective sphincter-sparing technique for treating HTAF. To confirm long-term outcomes, larger sample size prospective randomized controlled trials are required.